Construction of a dictionary of behaviors and generic skills essential for the diocesan priest in Peru - Swinnen Sardón, Jean-Paul (2014)
The present article is based on a previous study that provided a competencies-based profile of a Peruvian diocesan priest. It is of an exploratory and descriptive nature, and follows the qualitative research methodology. It seeks to establish the behaviors that are necessary for carrying out the pastoral work of a Peruvian diocesan priest. For that purpose, it carries out two studies. In the first one, it identifies five essential generic competencies: Interior Life, Obedience, Leading by Example, Priestly Fraternity and Continuous Education. In the second one, it creates and validates a behavioral dictionary for assessing levels of assimilation of each of the essential generic competencies. Moreover, it provides concrete and measurable indicators of the standard performance of a Peruvian diocesan priest.